2018
DOI: 10.1063/1.5019934
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the spin hall magnetoresistance in Cr2O3/Pt bilayers close to the Néel temperature

Abstract: We study the evolution of magnetoresistance with temperature in thin film bilayers consisting of platinum and the antiferromagnet Cr 2 O 3 with its easy axis out of the plane. We vary the temperature from 20 • C to 60 • C, close to the Néel temperature of Cr 2 O 3 of approximately 37 • C. The magnetoresistive response is recorded during rotations of the external magnetic field in three mutually orthogonal planes. A large magnetoresistance having a symmetry consistent with a positive spin Hall magnetoresistance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 29 publications
(45 reference statements)
4
65
0
Order By: Relevance
“…is shown in Figure 3(a-c) for different relative orientations of the magnetic field B and the current j. As a first general observation for all the three cases, we note that the MR monotonously decreases in absolute value when lowering the sample temperature, eventually displaying an almost flat response for T ≤ 40 K. This is a first signature of a magnetic phase transition from the paramagnetic to the antiferromagnetic state in t-Cr 2 O 3 , and a similar behavior can also be observed at the phase transition of Cr 2 O 3 in the corundum structure [11].…”
Section: Magnetoresistance and Hall Effectsupporting
confidence: 69%
“…is shown in Figure 3(a-c) for different relative orientations of the magnetic field B and the current j. As a first general observation for all the three cases, we note that the MR monotonously decreases in absolute value when lowering the sample temperature, eventually displaying an almost flat response for T ≤ 40 K. This is a first signature of a magnetic phase transition from the paramagnetic to the antiferromagnetic state in t-Cr 2 O 3 , and a similar behavior can also be observed at the phase transition of Cr 2 O 3 in the corundum structure [11].…”
Section: Magnetoresistance and Hall Effectsupporting
confidence: 69%
“…The SMR in bilayers of antiferromagnets/HM has been investigated only very recently. A positive SMR was claimed for bilayers of SrMnO3/Pt [19] and Cr2O3/W, [20] possibly due to a small canted/uncompensated magnetization M. [21] During the preparation of this work, reports on a positive SMR in paramagnetic Cr2O3/Pt, negative SMR in Cr2O3/Ta [22,23] and a negative SMR in NiO(111)/Pt bilayers, [24,25] where the magnetic field rotates in the NiO(111) easy plane only, in agreement with theoretical predictions [7], were published. during the preparation of this work.…”
Section: Introductionmentioning
confidence: 94%
“…The angular dependence additionally disputes long-range antiferromagnetic ordering in our bilayers, since a shift of the extrema by 90 deg compared to the SMR introduced in Eq.1 would be expected for an AFM. [10][11][12]18,24 The existence of a magnetoresistance in PMI/Pt heterostructures has already been reported above the Curie temperature for CoCr 2 O 4 /Pt bilayers with a MR ratio of ∆ρ/ρ 0 < 2 × 10 −6 by Aqeel et al 16 and above the Neel temperature for Cr 2 O 3 /Pt bilayer structures by Schlitz et al 18 with ∆ρ/ρ 0 > 1 × 10 −4 . It has also been reported that no MR was detectable in paramagnetic Gd 3 Ga 5 O 12 (GGG)/Pt heterostructures at room temperature.…”
mentioning
confidence: 92%
“…19 The presence of SMR has been reported by two a) Electronic mail: m.lammel@ifw-dresden.de b) Electronic mail: sebastian.goennenwein@tu-dresden.de groups in different magnetically ordered materials, in the paramagnetic phase above the ordering temperature. 16,18 Since the SMR is primarily studied in the magnetically ordered phase in those works, the authors do not provide a microscopic picture for the SMR in a randomly ordered spin ensemble. Therefore, in this work, we systematically study the SMR in a paramagnetic insulator (PMI)/spin Hall metal bilayer and critically compare the experimental results to the SMR expected from two different microscopic models: one model assumes an ensemble of noninteracting moments, while the other model considers the (induced) net magnetization.…”
mentioning
confidence: 99%